Critical loads of acidity for forest soils and relationship to forest decline in the northern Czech Republic - Akselsson, Cecilia; Ardö, Jonas; Sverdrup, Harald (Environmental monitoring and assessment, 2004)
Critical load calculations in the Czech part of 'the Black Triangle' show exceedance of critical load in 75% of the forest area. A comparison with forest damage data shows an insignificant tendency toward more forest damage in areas with high exceedance. We conclude that high exceedance of critical load is a probable contributing factor to forest damage in the area.
Keywords: Trees; Nitrogen; dusík; chemické modely; stromy; Environmental Monitoring; látky znečišťující půdu; Soil Pollutants; počasí; hliník; Weather; časové faktory; monitorování životního prostředí; Aluminum; Models, Chemical; Acids; Hydrogen-Ion Concentration; Czech Republic; Sulfur; síra; Česká republika; koncentrace vodíkových iontů; Time Factors; kyseliny